2008
DOI: 10.1142/s0218271808013960
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Statistics for Ordinary Particles in Quantum Gravity

Abstract: SUMMARYObjects exhibiting statistics other than the familiar Bose and Fermi ones are natural in theories with topologically nontrivial objects including geons, strings, and black holes. It is argued here from several viewpoints that the statistics of ordinary particles with which we are already familiar are likely to be modified due to quantum gravity effects. In particular, such modifications are argued to be present in loop quantum gravity and in any theory which represents spacetime in a fundamentally piece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
(62 reference statements)
0
6
0
3
Order By: Relevance
“…Notice that, using a different approach, some quantum gravity models have been advanced which are based on thermostatistics and condensed matter systems [10]. Moreover, it has even been suggested that for discrete systems in quantum gravity the spin-statistics theorem can be different from the usual one [11].…”
Section: Introductionmentioning
confidence: 99%
“…Notice that, using a different approach, some quantum gravity models have been advanced which are based on thermostatistics and condensed matter systems [10]. Moreover, it has even been suggested that for discrete systems in quantum gravity the spin-statistics theorem can be different from the usual one [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one has to bear in mind that the statistics of particles should be thought as a property of spacetime and particularly near the horizon of a Schwarzschild BH. Therefore, if spacetime is quantum by nature, the commutation or anticommutation relations for creation and annihilation operators, for the considered fields, may change [17]. Thus, exotic statistics and thereby a modification of the spin statistics theorem could be deeply related to the very quantum nature of spacetime and could emerge from an underlying theory of quantum gravity in the near vicinity of a BH horizon.…”
Section: Discussionmentioning
confidence: 99%
“…El conteo correcto de estos estados llevará a las estadísticas correspondientes de sistemas en este esquema de cuantización. Esto tendrá consecuencias sobre las propiedades de los sistemas, por ejemplo a través del teorema de espín-estadística [187]. Un indicio de las posibles modificaciones que se tendrían, por ejemplo en las estadísticas cuánticas es la expresión encontrada para el número de ocupación (5.60).…”
Section: Discussionunclassified
“…Se ha argumentado que las estadísticas modificadas pueden aparecer en la gravedad cuántica y las teorías discretas, sin embargo la relación entre la estructura discreta y la estadística sigue aún abierta [187].…”
Section: Correcciones Poliméricas a Magnitudes Termodinámicas De Sist...unclassified
See 1 more Smart Citation